CAR-T and nanotechnology: A comparative Perspective on autoimmune disease and cancer - A. Pavithra; C. Ragavendran (Advances in Biomarker Sciences and Technology)
Nanotechnology has emerged as a key transformative force in upgrading Chimeric Antigen Receptor T-cell (CAR-T) from generation to generation in cancer and autoimmune treatment. Nanotechnology-aided CAR-T therapy has shown its ability to overcome various challenges in contemporary CAR-T therapy. The comparative analysis of CAR-T and its applications in cancer and autoimmune diseases focuses on target specificity, with immune cells being used as “chaperones” for nanoparticles, Immunosuppressibility by modifying microarchitecture, prolonged cell viability, and other nanotechnological modifications has been briefly discussed. The latest and smartest innovations, such as nano-enzymes linked CAR, stimuli-responsive nanoparticles, nano-based dual-targeting CAR structures, and nano-cargos, have upgraded CAR-T therapy to its latest advancements. Despite regulatory compliance, and cost of production and utility of Nano-CAR-T can be overcome by the use of green nanotechnology. The aid of advancements in AIs, software, MLs etc offers promising solutions to hurdles in scalability. A number of clinical and preclinical trials in the last few years have been explained to highlight the current status of Nano-CAR-T in present-day treatment and for a promising future. This review emphasizes the novel role of nanotechnology in shaping the future of advanced CAR-T therapy, paving the way for milestones in medical research.